Integrating Restorative Justice and the Principle of Islah in the Reform of Indonesia’s Criminal Justice System - Nur Khasanah; Stevani Ameliya Putri; Venita Wulandari; Asrizal Saiin; Mashair Idris (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
The Indonesian criminal justice system continues to be predominantly shaped by a retributive paradigm that is centered on formal punishment and incarceration. This has resulted in various structural problems, including prison overcrowding, the ineffectiveness of penal sanctions, victim marginalization, and the weak orientation toward social recovery and communal harmony. These conditions indicate the urgent need for a more humane, restorative, and substantive paradigm of criminal justice reform. The present study aims to analyse the integration of restorative justice and the principle of islah in Islamic law as an alternative framework for reforming Indonesia's criminal justice system. The research employs normative legal research based on library research using conceptual, philosophical, statutory, and comparative approaches. The data were collected through a comprehensive review of extant literature on criminal law regulations, restorative justice doctrines, contemporary Islamic legal scholarship, fiqh jinayah, and maqasid al-syariah theories. These were analysed through a combination of interpretative and content analysis methods. The findings demonstrate that restorative justice and the principle of islah share substantial philosophical convergences in their orientation towards peacebuilding, reconciliation, restoration of social relations, community participation, and substantive justice. The principle of islah functions not merely as a conflict resolution mechanism within Islamic legal tradition, but also serves to strengthen the moral, social, and humanistic dimensions of restorative justice within Indonesia's religious and plural society. The present study proposes an integrative formulation between modern criminal law and contemporary Islamic legal values, positing these as a model for a more restorative, humane, and socially just criminal justice reform.